[OA056] Range uncertainty reduction in proton beam therapy via prompt gamma-ray detection. (August 2018) - Panaino, Costanza; Mackay, Ranald; Merchant, Michael; Green, Stuart; Phoenix, Ben; Price, Tony; Kirkby, Karen; Taylor, Michael
Abstract : Purpose: In proton therapy precise knowledge of the beam range is essential to guarantee the treatment's efficacy and to avoid unnecessary toxicities. Over a fractionated course of treatment anatomical changes can severely impact the delivered dose distribution from that planned; evaluation of these changes on a fraction-by-fraction basis is essential. We report the first results of a new method to determine proton beam range in three dimensions, for pencil-beam scanning systems, with an uncertainty below 3 mm. Methods: The range is determined through the reconstruction of the origin of prompt gamma (PG) rays emitted from nuclear de-excitations following proton bombardment. PG emission is almost instantaneous and is characterised by a high-production rate. The prototype system is comprised of 16 symmetrically-spaced LaBr3(Ce) detectors, in a spherical design. Initially the position reconstruction capability of the detector system was examined using Geant4 simulations. To determine the PG-rays emission positions in 3D, the information recorded by each detector is fed into a reconstruction algorithm, developed in the MATLAB environment. The development, testing and laboratory validation of the algorithm has been conducted using a sealed 60 Co source. Furthermore the algorithm has been employed to investigate, by means of Geant4 simulations, how the system performs with a proton pencil beam at different clinical energies. In the simulations a water phantom with 2-cm thick body materials slabs embedded inside has been modelled. Results: Preliminary simulation results show that for an ideal detector system the reconstruction algorithm is capable of determining the source position to within 1 mm in the 3D space. The algorithm is also able of discriminating between multiple sources with a relative separation of 0.15 mm. A good agreement has been observed between the dose and the prompt-gamma distribution from a proton pencil beam impinging the different phantoms at all the employed clinical energies. Conclusions: Proof-of-principle for the reconstruction algorithm with a sealed 60 Co source has been obtained. The response of the system with a clinical proton beam has been evaluated, by means on Monte Carlo simulations. The next stage is to test the system with a proton beam experimentally.